The innovative university : changing the DNA of higher education from the inside out changing the DNA of higher education from the inside out - Christensen, Clayton M.; Eyring, Henry J. (San Francisco : Jossey-Bass, 2011)
This work offers a hopeful vision to show universities how they can become more innovative, efficient, and true to their mission. It shows how higher education can respond to the forces of disruptive innovation that they are currently facing. The authors offer an analysis of where the traditional university and its traditions have come from and how it needs to change for the future. Through an examination of Harvard and Brigham Young University, Idaho as well as other stories of innovation in higher education, they decipher how universities can find innovative, less costly ways of performing their uniquely valuable functions. The book offers new ways forward to deal with curriculum, faculty issues, enrollment, retention, graduation rates, campus facility usage, and a host of other urgent issues in higher education. It discusses a strategic model to ensure economic vitality at the traditional university. It contains novel insights into the kind of change that is necessary to move institutions of higher education forward in innovative ways. To avoid the pitfalls of disruption and turn the scenario into a positive and productive one, universities must re-engineer their institutional DNA from the inside out. This book uncovers how the traditional university survives by breaking with tradition, but thrives by building on what it has done best. -- Provided by publisher.
Part I: Reframing the Higher Education Crisis: 1. The Educational Innovator's Dilemma: Threat of Danger, Reasons for Hope -- Part II: The Great American University: 2. Puritan College -- 3. Charles Eliot, Father of American Higher Education -- 4. Pioneer Academy -- 5. Revitalizing Harvard College -- 6. Struggling College -- 7. The Drive for Excellence -- 8. Four-Year Aspirations in Rexburg -- 9. Harvard's Growing Power and Profile -- 10. Staying Rooted -- Part III: Ripe for Disruption: 11. The Weight of the DNA -- 12. Even at Harvard -- 13. Vulnerable Institutions -- 14. Disruptive Competition -- Part IV: A New Kind of University: 15. A Unique University Design -- 16. Getting Started -- 17. Raising Quality -- 18. Lowering Cost -- 19. Serving More Students -- Part V: Genetic Reengineering: 20. New Models -- 21. Students and Subjects -- 22. Scholarship -- 23. New DNA -- 24. Change and the Indispensable University.
Includes bibliographical references and index.
Keywords: Universities and colleges -- United States; Educational change -- United States